Peningkatan kualitas akhlak berdasarkan buku hilyah thalabil ilmi dengan pendekatan tazkiyatunnufus (studi kasus santriwati MA Islamic Center Bin Baz) - Roidah Lina; Qiyadah Robbaniyah; Cyntia Rahmani (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
Morals are an important education for scientific prosecutors, so researchers want to research related to Improving the Quality of Morals Based on the Hilyah Thalabil Ilmi Book with the Tazkiyatunnufus Approach (Case Study of Santriwati MA Islamic Center Bin Baz). Qualitative research methods, observation data collection, interviews and documentation, data analysis. The results of this study are the book hilyah thalabil science written by Sheikh Bakr in 1408 H. then Sheikh Utsaimin gave a lecture on the book. The adab of a seeker of knowledge towards himself, namely first, seeking knowledge is worship of Allah. Terms of worship in studying knowledge (sincere and feeling watched by God). Second, the manners of making friends; choose good friends and friends who can have a good influence on him and stay away from friends who invite you to waste time or invite you to disobedience. Tazkiyatun nufus is recommended for a Muslim who wants to always draw closer to Allah and really helps educators in solving students' moral problems. By knowing the heart, muhasabah, and patience. Improving the morals of students with the tazkiyatun nufus approach, first: giving material about morals to oneself and how to choose good friends according to the hilyah book and mentoring through intense discussion interactions related to a clean heart. Second: santiwati is led and accompanied from the depths of her heart in carrying out the values ​​highlighted through the tazkiyatunnufus approach, namely about how the heart gets God's blessing and the blessings of knowledge that can be obtained at Islamic boarding schools. From the results of this assistance, female students have started to find their identity to be better and their enthusiasm for studying has increased, their worship has become more diligent, and they can choose friends who are more productive in inviting them to goodness.